PENGARUH TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH DAN SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH PADA OPD KOTA SURABAYA - Sari, Octavia Dwi Sagita; Hidayat, M. Taufiq (UNIKA Santo Thomas, 2025)
This study aims to determine the effect of Transparency of Regional Financial Management and Internal Control System on Accountability of Government Agency Performance in Regional Apparatus Organization (OPD) of Surabaya City. This study uses quantitative methods. This study uses primary data by distributing 85 questionnaires to respondents in 17 Surabaya City Offices, but only 72 questionnaires were returned by respondents. The data analysis technique uses descriptive statistical analysis with SPSS test tools. The results of this study indicate that the variable Transparency of Regional Financial Management affects Accountability of Government Agency Performance and Internal Control System affects Accountability of Government Agency Performance. Transparency of Regional Financial Management and Internal Control System simultaneously affect Accountability of Government Agency Performance.